2022
DOI: 10.1111/cas.15372
|View full text |Cite
|
Sign up to set email alerts
|

miR‐3184‐3p enriched in cerebrospinal fluid exosomes contributes to progression of glioma and promotes M2‐like macrophage polarization

Abstract: Liquid biopsy is a novel strategy for tumour diagnosis. The contents of cerebrospinal fluid (CSF) exosomes could reflect glioma status, hence sampling exosomes from CSF is a means of liquid biopsy for glioma. However, few studies have focused on the function of microRNAs in CSF exosomes. In this study, we found that miR‐3184‐3p was enriched in CSF exosomes in glioma patients and was downregulated after tumour resection. We found that miR‐3184 facilitates glioma progression in two ways. On the one hand, miR‐318… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Exosomes, as emerging stars in liquid biopsy, exhibit unique advantages in the diagnosis of various cancers [28] . Firstly, exosomes can be produced by various cells and are found in various body uids, such as blood, urine [29] , breast milk [30] , saliva [31] , cerebrospinal [32] uid, and tears. Secondly, exosomes are abundant and easily accessible; there are approximately 10 12 exosomes in 1 ml of blood, and various techniques like ultracentrifugation, ultra ltration, and exosome isolation kits are widely used for exosome extraction.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes, as emerging stars in liquid biopsy, exhibit unique advantages in the diagnosis of various cancers [28] . Firstly, exosomes can be produced by various cells and are found in various body uids, such as blood, urine [29] , breast milk [30] , saliva [31] , cerebrospinal [32] uid, and tears. Secondly, exosomes are abundant and easily accessible; there are approximately 10 12 exosomes in 1 ml of blood, and various techniques like ultracentrifugation, ultra ltration, and exosome isolation kits are widely used for exosome extraction.…”
Section: Discussionmentioning
confidence: 99%
“…38 CSF RNA has been quantified using PCR, microRNA arrays, [39][40][41] and RNA-seq. 38,[42][43][44][45][46] Most commercial RNA extraction kits isolate similar CSF RNA yields. 38,47 Meanwhile, choice of quantification is application-dependent; small RNA-seq is optimal for high-throughput untargeted discovery, reverse transcriptase quantitative polymerase chain reactions arrays for larger targeted panels, and ddPCR for sensitive quantification of individual RNA targets.…”
Section: Types Of Csf Biomarkers-a Brief Overviewmentioning
confidence: 99%
“…27,66,[78][79][80][81][82] Following the same logic, biomarkers have also been correlated with treatment response, 80,[83][84][85][86][87][88][89][90][91][92][93][94][95] and decline after surgical resection. 44,46,[96][97][98][99][100] More direct methods of establishing neoplastic origins involve spatial localization of biomarkers using immunohistochemistry or in situ hybridization (Data Supplement, Table S3). 101 Single-cell transcriptomic sequencing can also establish cell origin of RNA and proteomic biomarkers.…”
Section: Tumor Specificity and The Cell-of-origin Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…The cerebrospinal fluid (CSF) that envelops the brain and spinal cord is predominantly produced by the choroid plexus within the brain’s ventricles. CSF-Exos have been explored as potential diagnostic and prognostic markers for CNS disorders [ 68 , 69 ]. Moreover, additional studies have demonstrated that externally introduced CSF-Exos may modify neurological functions following SCI.…”
Section: Neurologically Derived Exosomes For Neurotrauma Therapymentioning
confidence: 99%